2014
DOI: 10.1038/ncomms4216
|View full text |Cite
|
Sign up to set email alerts
|

A Polymerase Theta-dependent repair pathway suppresses extensive genomic instability at endogenous G4 DNA sites

Abstract: Genomes contain many sequences that are intrinsically difficult to replicate. Tracts of tandem guanines, for instance, have the potential to adopt stable G-quadruplex structures, which are prone to cause genome alterations. Here we describe G4 DNA-induced mutagenesis in Caenorhabditis elegans and identify a non-canonical DNA break repair mechanism that generates deletions characterized by an extremely narrow size distribution, minimal homology of exactly one nucleotide at the junctions, and by the occasional p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
218
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(235 citation statements)
references
References 46 publications
(55 reference statements)
14
218
0
1
Order By: Relevance
“…Polθ has multiple documented activities in DNA replication and repair, including alt-EJ, replication repair, translesion synthesis, and replication initiation (4)(5)(6)(7)(8)10,15,31,32). Although the activities and cellular functions of Polθ-polymerase have been investigated, little is understood regarding the enzymatic activities of Polθ-helicase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polθ has multiple documented activities in DNA replication and repair, including alt-EJ, replication repair, translesion synthesis, and replication initiation (4)(5)(6)(7)(8)10,15,31,32). Although the activities and cellular functions of Polθ-polymerase have been investigated, little is understood regarding the enzymatic activities of Polθ-helicase.…”
Section: Discussionmentioning
confidence: 99%
“…1a) (1)(2)(3). Understanding the biochemical activities and cellular functions of Polθ have become a priority because it has been found to be essential for the error-prone doublestrand break (DSB) repair pathway known as microhomology-mediated end-joining (MMEJ) or alternative end-joining (alt-EJ) (3)(4)(5)(6)(7)(8)(9). Remarkably, Polθ expression has also been shown to be important for the proliferation of cells deficient in the homologous recombination (HR) pathway, such as due to mutations in BRCA1 or BRCA2 (4,10).…”
mentioning
confidence: 99%
“…Pol θ is important for MMEJ repair of DSBs in many organisms, including Drosophila, Caenorhabditis elegans, zebrafish, and mice. In C. elegans, it is essential for repair of DSBs located at the site of collapsed replication forks (17). Pol θ and other replication-related genes are frequently overexpressed in a number of cancer types and high levels of Pol θ expression strongly correlate to poor patient survival (18).…”
Section: Absence Of Pol θ Perturbs Chorion Gene Transcription and Eggmentioning
confidence: 99%
“…Using classic genetic methods, mutation frequencies have also been estimated in response to ionizing radiation (Rosenbluth et al 1985) and as a consequence of DNA repair deficiencies in the dog-1 helicase and the mrt-2 and clk-2 checkpoint genes (Harris et al 2006;Kruisselbrink et al 2008;Zhao et al 2008). Moreover, limited genome sequencing was used to estimate mutation rates in C. elegans (Cheung et al 2002;Denver et al 2006Denver et al , 2009Harris et al 2006) and studies were more recently extended genome-wide to strains deficient for translesion polymerases (Koole et al 2014;Roerink et al 2014). An initial study focused on yeast mutant accumulation, provided a baseline mutation rate, and showed increased mutagenesis for several repair deficiencies (Serero et al 2014).…”
mentioning
confidence: 99%